Impact Craters in South America - Acevedo, Rogelio Daniel; Rocca, Maximiliano C. L.; Ponce, Juan Federico; Stinco, Sergio G. (SpringerBriefs in Earth System Sciences,, 2015)
A complete and updated catalogue of impact craters and structures in South America from 2014 is presented here. Approximately eighty proven, suspected and disproven structures have been identified by several sources in this continent. All the impact sites of this large continent have been exhaustively reviewed: the proved ones, the possible ones and some very doubtful. Many sites remain without a clear geological "in situ" confirmation and some of them could be even rejected. Argentina and Brazil are leading the list containing almost everything detected. In Bolivia, Chile, Colombia, Guyana, Paraguay, Perú, Uruguay and Venezuela only a few were observed. Only Ecuador is waiting for new discoveries. So far, the largest well stated impact site is still the Araguainha structure in Brazil with its 40 kilometers in diameter. However, two possible impact structures are larger than Araguainha: Malvinas, (with 250 kilometers in diameter) and Vichada in Colombia, (50 kilometers). This study also reports the existence of some Tertiary-Quaternary glassy impactite layers: the "escorias" and "tierras cocidas" of the pampas in Argentina.